Effects of dietary proanthocyanidin supplementation on growth performance, immune function, antioxidant capacity, and gut microbiota in weaned pigs - Qiao, Yong; Liu, Jiahao; Xie, Kunhong; Yu, Bing; Luo, Yuheng; Zheng, Ping; Mao, Xiangbing; Yan, Hui; He, Jun (Frontiers in Microbiology, 2026)
IntroductionProanthocyanidin (PRO), a widely consumed type of dietary polyphenolic compound, exhibits diverse health-promoting properties due to its structure rich in abundant hydroxyl groups. However, the effects of dietary PRO supplementation on growth performance, immune function, antioxidant capacity, and gut microbiota in weaned piglets remain unexplored.MethodsIn this study, 800 hybrid barrows of Duroc × Landrace × Yorkshire (DLY) piglets, aged 28 days and with an average body weight of 9.40 ± 0.14 kg, were randomly assigned to five groups. Each group of piglets was continuously administered one of the following five dietary treatments: a basal diet (control group) or the basal diet supplemented with PRO at different doses of 15 mg, 30 mg, 60 mg, or 120 mg per kilogram of feed for 28 days.ResultsOn day 29, dietary PRO treatment showed a dose-dependent improvement in average daily gain (ADG, linear, p = 0.042), average daily feed intake (ADFI, linear, p = 0.078), and the digestibility of nutrients, including dry matter (DM), crude protein (CP), crude fat (EE), and gross energy (GE) (p < 0.05). Compared to the control group, PRO supplementation linearly reduced (p < 0.05) the concentrations of proinflammatory cytokines such as tumor necrosis factor alpha (TNF-α), interleukin-1 beta (IL-1β), and interleukin 6 (IL-6). In contrast, the levels of serum immunoglobulins, such as IgG, IgA, and IgM, as well as the activities of GSH and T-AOC, were linearly elevated (p < 0.05) by PRO supplementation in the piglet diet. In addition, dietary supplementation with 30 mg/kg PRO not only increased the abundance of butyrateproducing bacteria, such as Fournierella, Oscillospira, NK4A214_group, and UCG-005, at the species level but also tended to elevate (p < 0.1) the concentration of butyrate in the rectum.ConclusionsThese results suggest that PRO-containing feed might be a potential dietary strategy for improving gut homeostasis and overall health in weaned pigs.